Tumor resection with carmustine wafer placement as salvage therapy after local failure of radiosurgery for brain metastasis. Issue 3 (March 2015) - Mu, Frank; Lucas, John T.; Watts, Jonathan M.; Johnson, Annette J.; Daniel Bourland, J.; Laxton, Adrian W.; Chan, Michael D.; Tatter, Stephen B.
Abstract Prolonged survival in brain metastasis patients increases recurrence rates and places added importance on salvage therapies. Research examining carmustine polymer wafers as an adjuvant therapy for brain metastasis is limited. We present a single institution retrospective series documenting the use of BCNU wafers placed in the cavity of resected recurrent brain metastases that had failed prior stereotactic radiosurgery (SRS). Between February 2002 and April 2013, a total of 31 patients with brain metastases failed SRS and underwent resection with intracavitary placement of carmustine wafers. Clinical outcomes including local control, survival, cause of death, and toxicity were determined from electronic medical records. Kaplan–Meier analysis was performed to assess local control and survival. Imaging features were reviewed and described for patients with serial post-operative follow-up imaging examinations over time. Overall survival at 6 months and 12 months was 63% and 36%, respectively. Fourteen of 31 patients (45%) died from neurologic causes. Local control within the resection cavity was 87% and 70% at 6 and 12 months, respectively. Five patients (16%) underwent further salvage therapy following carmustine wafer placement after local failure. Resection cavities of all six patients with follow-up imaging showed linear peripheral enhancement. Pericavity and wafer enhancement was present as early as the same day as surgery and persisted in all cases to 6 months or longer. Carmustine polymer wafers are an effective salvage treatment following resection of a brain metastasis that has failed prior SRS. For patients with successful local control after wafer implantation, linear enhancement at the cavity is common.